Towards a Sustainable Campus: Performance and Economic Analysis of a Rooftop Solar power System for an IIUM Campus Building - Aiman Hakeemi; Moumen Idres (International Journal of Integrated Engineering, 2026)
This study presents the design and techno-economic analysis of a grid-connected rooftop solar photovoltaic (PV) system for an IIUM campus building using PVsyst software. The system modeling accounts for key loss factors, including temperature effects, shading, soiling (dust accumulation), and inverter inefficiencies. To validate the simulation approach, results were replicated from a reference study involving a 16.2?kWp PV system. For the IIUM campus building, nine configurations were assessed, combining three rooftop areas (1,200?m², 1,400?m², and 1,600?m²) with three PV module power ratings (535?Wp, 575?Wp, and 615?Wp). Among these, Design 7 (535?Wp modules with a 1,600?m² area) demonstrated the best overall performance, delivering an annual energy output of 362,151?kWh, a payback period of 7.4 years, and the lowest levelized cost of energy at RM?0.14 per kWh.